Introduction of carrier interference to spread spectrum multiple access - Nassar, C.R.; Natarajan, Bala; Shattil, S. (Institute of Electrical and Electronics Engineers, 2002)
This paper introduces a new scheme for spread spectrum multiple access. Like MC-CDMA, this scheme accomplishes spectral spreading by transmission of identical data over N carriers simultaneously. However, unlike any existing CDMA technique to date, this method supports user orthogonality not through the use of spreading codes (based on PN sequences), but rather through multiple carrier interference. Specifically, in this novel method, aptly named CIMA (carrier interference multiple access), the interference of multiple carriers enables user orthogonality or pseudo orthogonality based on user positioning in time. It is shown that CIMA supports simplified receiver structures for AWGN channels, and offers performance benefits in AWGN and fading environments
Keywords: AWGN channels; Fading channels; Interference (signal); Mobile radio; Radio receivers; Spread spectrum communication